EDEN ISS - A Space Greenhouse Analogue in Antarctica - Zabel, Paul (2018)
EDEN ISS is a European project focused on advancing bio-regenerative life support systems, in particular plant cultivation technologies and procedures for space and planetary habitats. Essential Controlled Environment Agriculture technologies were designed, developed and integrated within a Mobile Test Facility, consisting of two interconnected 20 ft shipping containers. The main EDEN ISS cultivation area is called the Future Exploration Greenhouse and is designed as a single cultivation room with unified environmental settings and a 17:7 h light-dark photoperiod. During an analogue test mission at the German Neumayer III research station in Antarctica, the greenhouse provides a variety of fresh pick-and-eat crops for the overwintering crew of 10 members. This is of particular importance during their 6-7 months long isolation phase, when no plane or ship resupply of the station occurs. This paper provides an overview of the as-built design configuration and outlines the main steps of the assembly, integration and test phase that took place between October 2016 and September 2017. Further, insight into the preparation procedures for the Antarctic mission is given, which led to the final mission preparation and transport logistics of the test facility. In December 2017, the analogue mission officially started with the on-site installation of the facility at Neumayer Station III. The presentation gives an overview of the on-site build-up phase and the activities involved in putting the facility into its nominal operations mode. The presentation concludes with a lessons learned and off-nominal issue section, gathered during the first months of operation in Antarctica.